PENDIDIKAN AGAMA HINDU PADA PAUD DAN INTERNALISASI MODERASI BERAGAMA DALAM PERSPEKTIF TRI HITA KARANA - Gunada, I Wayan Agus; Sutajaya, I Made (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Education is a conscious and planned effort to achieve competence, while Hindu education has two dimensions. Firstly, religious education is a form of transfer of religious knowledge to students. Secondly, Hindu religious education is a transformation of knowledge to improve sradha and bhakti and strengthen character. Today, radical understanding is a threat to watch out for. Thus, religious moderation is a solution to building religious harmony. Hindu religious education is one of the foundations of human values that strengthens religious moderation, especially in early childhood education. So, in a plural life, a universal value and concept are needed, which does not only lean towards one side, tri hita karana. The method used is a literature review, where data is analyzed by reviewing relevant libraries related to tri hita karana. Based on the literature review results, important things were obtained related to Hindu religious education, religious moderation, and Tri hita karana. In the concept of parhyangan, religious education in Early Childhood Education aims at paramartha, that education is directed towards achieving spiritual awareness. In contrast, in religious moderation, parhyangan seeks to provide reinforcement that every religion has the same belief in worshiping God. In the concept of pawongan and palemahan, religious education in Early Childhood Education to realize parartha can live in the world, side by side with others, and in religious moderation, pawongan reinforces that moderation does not change religion but changes excessive religious behavior, so the purpose of religious moderation is to glorify humans to build harmonious relationships. This study is expected to be theoretical and practical, especially as a reference library for relevant studies in the future.